Discovery research and development history of the dopamine D2 receptor partial agonists, aripiprazole and brexpiprazole - Tetsuro Kikuchi; Kenji Maeda; Mikio Suzuki; Tsuyoshi Hirose; Takashi Futamura; Robert D. McQuade (Wiley, 2021)
Abstract Otsuka Pharmaceutical Co., Ltd. successfully developed the first dopamine D2 receptor partial agonist approved for schizophrenia, the antipsychotic aripiprazole (Abilify®). The drug was approved for this indication in the United States in 2002 and has received approval in the United States, Europe, Japan, and many other countries for several indications including schizophrenia, acute mania, adjunctive treatment of major depressive disorder (MDD), irritability associated with autistic disorder, and Tourette's disorder. Otsuka next developed brexpiprazole (Rexulti®), another D2 receptor partial agonist, which was granted marketing approval in the United States in 2015 as adjunctive therapy in major depressive disorder and for the treatment of schizophrenia. In Japan, brexpiprazole also received approval as a treatment for schizophrenia in 2018. In this review, we describe Otsuka's research history and achievements over the preceding 40 years in the area of antipsychotic drug discovery for dopamine D2 receptor partial agonists.